Characterization of semiconductor heterostructures - Wong, Qihao. (2012)
Strain accelerated HF etching is a process which allows for the separation of an intermediate layer in an aqueous acidic solution. The key idea behind this etching method is to induce tensile strain on the material which will subsequently improve the rate of etching. The initial stage of this project requires the student to search and purchase an ideal stepper motor which meets the specific requirement to induce sufficient strain on the intermediate layer. Upon purchase, the student has to understand the device and program the device‘s function to meet the requirements of the experiment. On top of that, the student will implement the device into the experiment, and study the effects it has on the results.